Peripheral retinal ischaemia, as evaluated by ultra-widefield fluorescein angiography, is associated with diabetic macular oedema. Issue 5 (15th March 2012) - Wessel, Matthew M; Nair, Nandini; Aaker, Grant D; Ehrlich, Joshua R; D'Amico, Donald J; Kiss, Szilárd
Abstract : Purpose: To determine the relationship between retinal ischaemia and the presence of macular oedema (DMO) in patients with diabetic retinopathy (DR) using ultra-widefield fluorescein angiography (UWFA) imaging. Methods: A retrospective review of 122 eyes of 70 treatment-naïve diabetic patients who underwent diagnostic UWFA using the Optos 200Tx imaging system. Two independent, masked graders quantified the area of retinal ischaemia. Based on clinical examination and optical coherence tomography (OCT), each patient was given a binary classification as either having DMO or no DMO. McNemar's test (with Yates' correction as indicated) and a two-sample test of proportions were used to determine the relationship between DMO and ischaemia for binary and proportional data, respectively. Linear and logistic models were constructed using generalised estimating equations to test relationships between independent variables, covariates and outcomes while controlling for inter-eye correlation, age, gender, haemoglobin A1c, mean arterial pressure and dependence on insulin. Results: Seventy-six eyes (62%) exhibited areas of retinal ischaemia. There was a significant direct correlation between DMO and peripheral retinal ischaemia as seen on UWFA (p<0.001). In addition, patients with retinal ischaemia had 3.75 times increased odds of having DMO compared with those without retinal ischaemia (CI 1.26 to 11.13, p<0.02). Conclusion: Retinal ischaemia is significantly correlated with DMO in treatment-naïve patients with DR. UWFA is a useful tool for detecting peripheral retinal ischaemia, which may have direct implications in the diagnosis, follow-up and treatment such as targeted peripheral photocoagulation.